2019
DOI: 10.1111/irj.12238
|View full text |Cite
|
Sign up to set email alerts
|

Reducing carbon emissions through employee participation: evidence from Australia

Abstract: Based on a survey of 682 Australian organisations, we find that employee participation influences organisations' behaviours to reduce carbon emissions. Representative forms of participation and mechanisms dedicated specifically to environmental management are particularly important. Utilisation of a range of forms of participation is also associated with a broader suite of emission reduction activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…An increasingly dire issue regarding the environment currently is its rapid degradation. The main causes are the depletion of natural resources and also other human interventions, such as disproportionate cutting of trees and burning of fossil fuel, which have resulted in carbon emission (Fawehinmi et al, 2020;Gao et al, 2017;Yang et al, 2016), consequently leading to natural disasters and climate change that are negatively affecting people's quality of life and organizations alike (Lukman et al, 2013;Markey et al, 2019;Zhang et al, 2018). As part of countermeasures, most governments, including those of developing countries, have made pledges to global movements, such as AGENDA 2030 (United Nations, 2015), and placed environmental sustainability at the top of their to-do list.…”
Section: Introductionmentioning
confidence: 99%
“…An increasingly dire issue regarding the environment currently is its rapid degradation. The main causes are the depletion of natural resources and also other human interventions, such as disproportionate cutting of trees and burning of fossil fuel, which have resulted in carbon emission (Fawehinmi et al, 2020;Gao et al, 2017;Yang et al, 2016), consequently leading to natural disasters and climate change that are negatively affecting people's quality of life and organizations alike (Lukman et al, 2013;Markey et al, 2019;Zhang et al, 2018). As part of countermeasures, most governments, including those of developing countries, have made pledges to global movements, such as AGENDA 2030 (United Nations, 2015), and placed environmental sustainability at the top of their to-do list.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it contributes to the individual level by improving work-life balance and job performance [40]. Previous studies have demonstrated that employee participation is a common practice in the field of SHRM and is considered a competitive advantage for sustainability success [32,41,42]. However, in the literature, little is known about whether the sustainable approach of organizations enhances a participatory environment in issues in addition to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The suitability of this framework for exploring employee voice within sustainable HRM is reinforced by the research of Markey et al [10,45]. Their research found support for Cox et al's [21] findings that the breadth and depth of employee voice mechanisms is important within the context of carbon reduction strategies across a range of Australian organisations.…”
Section: Implications and Future Research Directionsmentioning
confidence: 92%
“…While the research finds that employees do affect environmental outcomes through Green HRM, a gap in the literature exists in the consideration of how employees can voice and be part of the drive towards and development of, environmental initiatives. An excep-tion is Markey et al [10,45], who found that employee participation in reducing carbon emission strategies is important, and also that the nature of the employee participation schemes, in terms of quality and quantity, matters. Such a finding within the Green HRM domain of sustainability adds support to our argument that both the role, and the type, of employee voice mechanisms needs to be conceptualised within the growing sustainable HRM literature.…”
Section: The Employee and Sustainable Hrmmentioning
confidence: 99%
See 1 more Smart Citation